2018
DOI: 10.1121/1.5043384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phonatory characteristics using ex vivo rabbit larynges

Abstract: Quantitative analysis of phonatory characteristics of rabbits has been widely neglected. However, preliminary studies established the rabbit larynx as a potential model of human phonation. This study reports quantitative data on phonation using ex vivo rabbit larynx models to achieve more insight into dependencies of three main components of the phonation process, including airflow, vocal fold dynamics, and the acoustic output. Sustained phonation was induced in 11 ex vivo rabbit larynges. For 414 phonatory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 64 publications
12
37
4
Order By: Relevance
“…The data acquisition was already previously described in detail [39]; hence the following is only a short overview of the experimental setup and data collection. For detailed information, we refer to the reference study on type 1 oscillations [39]. Data from 11 ex vivo rabbit larynges (New Zealand White, 4-5 kg body weight, ages 14-118 weeks) were used for this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data acquisition was already previously described in detail [39]; hence the following is only a short overview of the experimental setup and data collection. For detailed information, we refer to the reference study on type 1 oscillations [39]. Data from 11 ex vivo rabbit larynges (New Zealand White, 4-5 kg body weight, ages 14-118 weeks) were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that increasing airflow and elongation affected subglottal pressure, fundamental frequency, sound pressure level (SPL) and the vibratory amplitude. In 2018, Döllinger et al [39] performed the first systematic study on ex vivo rabbit larynges, analyzing HSI, audio and subglottal pressure data and the influence of glottal gap characteristics on the phonatory process, as such comprehensive analyses were missing in the literature. Significant influences of applied airflow and the vocal fold elongation level on vocal fold closure insufficiency were detected [40,41].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such differences can be partly attributed to broader cochlear tuning in rabbit, as shown in Figure 7F by the comparison of 10-dB bandwidths of rabbit ANF (Borg et al, 1988) with estimates of human AN bandwidths from compound action potentials (Verschooten et al, 2018). Extrapolating the trends in human AN bandwidths to lower CFs, the bandwidths of neurons with CFs in the first formant region (200-800 Hz) may be narrow enough to resolve harmonics of F0s in the range of male voices, and this would also be true for human IC neurons if the sharpening observed in the rabbit IC also occurs in humans The few available studies on rabbit phonation suggest F0s in the range of 500-1200 Hz (Swanson et al, 2010;Mills et al, 2017;Döllinger et al, 2018), which is at the low end of the effective range for rate-place coding by IC neurons.…”
Section: Implication For Pitch Perceptionmentioning
confidence: 99%